Occupational radiation exposure and excess additive risk of cataract incidence in a cohort of US radiologic technologists. (2nd December 2019) - Little, Mark P; Cahoon, Elizabeth K; Kitahara, Cari M; Simon, Steven L; Hamada, Nobuyuki; Linet, Martha S
Abstract : Objectives: Previous analyses of cataract in radiation-exposed populations have assessed relative risk; radiogenic excess additive risk (EAR), arguably of more public health importance, has not been estimated. Previous analysis of a large prospective cohort of US radiologic technologists (USRT) quantified excess relative risk of cataract in relation to occupational radiation dose. We aim to assess EARs of cataract. Methods: We estimated EARs of cataract/cataract surgery in the USRT cohort using generalised additive models in relation to occupational radiation exposure, and assessed risk modification by a priori-selected cataract risk factors (diabetes, body mass index, smoking, race, sex, birth-year, ultraviolet B (UVB) radiation exposure). Results: There were 11 345 cataract diagnoses and 5440 of cataract surgery during 832 462 and 888 402 person-years of follow-up, respectively. Cumulative occupational radiation exposure was associated with self-reported cataract, but not with cataract surgery, with EAR/10 4 person-year Gy=94 (95% CI: 47 to 143, p<0.001) and EAR/10 4 person-year Gy=13 (95% CI: <0 to 57, p=0.551), respectively. There was marked (p<0.001) variation of EAR by age and by diabetes status, with risk higher among persons ≥75 years and diabetics. There were indications of elevated risk among those with higher UVB radiation (p=0.045), whites (p=0.056) and among those with higher levels of cigarette smoking (p=0.062). Elevated additive risk was observed for estimated occupational radiation eye-lens doses <100 mGy (p=0.004) with no dose–response curvature (p=0.903). Conclusions: The elevated additive risks associated with low-dose radiation, if confirmed elsewhere, have important public health and clinical implications for radiation workers as well as regulatory measures.